Craft as cultural ecologically located practice: Comparative case studies of textile crafts in Cyprus, Estonia and Peru. Issue 2 (1st September 2017) - Dillon, Patrick; Kokko, Sirpa
This article reports comparative case studies in three countries: Estonia, Cyprus and Peru. Through these, the cultural ecologies of six textile craft practitioners, two in each country, were investigated using an interview-based situational analysis. Cultural ecology is concerned with transactional relationships between people and the environments that they inhabit. It provides a lens on the processes of continuity and change that shape cultural patterns and cultural traditions. Interviews were conducted in open format around questions about biographical and professional practice. Relationships between practitioners' personal histories and their craft practices were explored. Outcomes suggest that the cultural ecologies are profoundly shaped by the transmission of customs, beliefs and values from generation to generation, which, in turn, are located within a place of social interaction conferring a sense of belonging and an environment for the formation of social identities. These attachments powerfully influence continuity in the craft traditions. The interrelated processes of globalization and technological development are the dominant agents of change. Responses to these pressures vary with the practitioners in the three countries and are linked to factors associated with cultural resilience.